Integration processes in geography and its place in the system of sciences - Viktor Alexandrovich Shalnev; Ekaterina Aleksandrovna Lyashenko (Наука. Инновации. Технологии, 2022)
In article one of the directions of consolidation of the processes of integration connected with development of theoretical fundamentals of the general geography, her hosts of concepts and categorial concepts uniform for all family of geographical sciences is offered. The central place is taken here by the doctrine about a geoversuma as the general object of studying, and the geographical environment playing a large role in life and development of society. Spatial approach and the concept of geographical space, evolutionary approach and history of formation of geographical reality, the concept of culture genesis and the civilization worlds of society, system approach and doctrines about the geosystems of the modern landscape sphere are considered by the main approaches and concepts of such geography (natural, public, partial and integrated). Special attention is paid to a concept of the environment of the place of human life taking into account certain types of his activity.